문제음주자의 절주의도 영향 요인 - 강경화(Kyonghwa Kang); 김성재(Sungjae Kim) (Seuteureseu yeon-gu (Online), 2014)
본 연구는 2010년 한국음주문화연구센터의 음주 실태 및 음주 문제에 대한 국민 인식 조사 연구의 자료를 활용하여19세 이상 성인 문제 음주자의 절주의도에 영향을 미치는 요인을 파악하고자 하였다. 이를 위해 알코올사용장애 선별 검사(Alcohol Use Disorder Identification Test: AUDIT) 12점 이상을 문제음주로 하고 변화단계 알고리즘을 절주의도로 분석하였다. 연구 결과, 문제음주자의 66.2%는 향후 6개월내에 적절한 음주 행위로의 변화를 고려하지 않는 숙고전단계에 속하는 것으로 나타났다. 절주의도는 긍정적 음주결과기대, 음주거절 효능감, 주변사람의 음주행위 지각, AUDIT 총점, 운동 여부에 따라 통계적으로 유의한 차이를 보였다. 긍정적 음주결과기대(OR: 1.145 p=.002)와 음주거절 효능감(OR: 1.139, p=.001)은 준비단계에 비하여 숙고전단계에 정적(＋)인 영향을 주었다. 음주거절 효능감(OR: 1.163, p＜.001)과 주변 사람의 음주여부 지각(OR: 0.386, p=.001)은 준비단계에 비하여 숙고 단계에 정적(＋) 영향력을 미쳤다. 본 연구는 문제음주자의 절주의도를 위한 주요 요인으로 음주거절 효능감과 긍정적 음주결과기대 뿐아니라 주변사람의 음주행위 지각도 확인하였다. 향후 음주로 기대하는 결과와 음주 규범에 대한 인지적 믿음의교정과 음주거절 기술을 향상시키기 위한 동기강화 개별 중재 프로그램의 개발과 음주 규범을 측정할 수 있는 도구개발이 필요함을 제안한다. This study was to investigate affecting factors of intention to responsible drinking in problem drinkers. The secondary data from the 2010 KARF Drinking Patterns and Alcohol Problems Survey were used. The subjects were 343 problem drinkers who scored more than 12 points in Alcohol Use Disorder Identification Test (AUDIT) from the data. Stage of Change used as the measurement for intention to responsible drinking. Other instruments were the Decisional Balance (DB), Drinking Refusal Self Efficacy (DRSE). The results showed that 66.2 % of all the subjects were the lowest intention to responsible drinking as classified in pre-contemplation stage. Intention to responsible drinking showed significant differences according to DB, DRSE, perceived amount of peer drinker, depression, AUDIT score and exercise. Compared to the preparation stage, positive Pros (OR: 1.145 p=.002) and DRSE (OR: 1.139, p=.001) were significant predictors of intention to responsible drinking in pre-contemplation stage. This study was identified not only DRSE, Pros but also perceived amount of peer drinker as main factors　of problem drinker's intention to responsible drinking. While compared to the preparation stage, DRSE (OR: 1.163, p＜.001) and perceive amount of peer drinker (OR: 0.386, p=.001) were significantly predicted the intention to responsible drinking in contemplation stage. This study suggested that more efforts to improve the problem drinkers intention to drinking refusal and to change the belief of drinking. Also, the development of an instrument is needed to measure social norms for drinking. KCI Citation Count: 10